2020
DOI: 10.3390/agronomy10101564
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock Influence on Growth and Mineral Content of Citrus limon and Citrus sinensis cv. Valencia Inoculated with Candidatus Liberibacter Asiaticus

Abstract: Huanglongbing (HLB) reduces the growth and development of citrus and induces changes in secondary metabolites such as flavonoids, limonoids, and polyamines. Likewise, infected plants have a deficient absorption of nutrients such as zinc, potassium, manganese, and copper. Therefore, the objective of this study was to evaluate the influence of different rootstocks on morphology and mineral changes of Citrus limon and Citrus sinensis cv. Valencia plants inoculated with Candidatus Liberibacter asiaticus. In a gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…As it is noted in the above-mentioned results, lemon trees grafted on Citrus aurantium were the most responsive to organic fertilization and the accumulation of most of the macro and micro elements, followed by orange trees grafted on the same rootstock, while it was noted that mandarin trees grafted on Citrus aurantium were the least responsive among the three types, and this may be due to the effect of the rootstock [14]. The results agree with [15] in the effect of the rootstock on the efficiency of the use of elements in lemon seedlings grafted on different citrus roots, and with [16], In the difference rootstock effect on the leaf mineral content, as they indicated a significant Fe accumulation increase in orange leaves than in lemon, this was attributed to the rootstock affect. Organic waste greatly affects the physical and chemical properties and fertility of the soil, as it enriches it with the elements that are necessary for the growth of plants, as well as the temporary change of soil acidity and affecting its buffering capacity, which due to absorb microelements, especially in the base soils [17], this may explain the plants leaf content of both macro and micro elements, as the tables indicate.…”
Section: Discussionsupporting
confidence: 68%
“…As it is noted in the above-mentioned results, lemon trees grafted on Citrus aurantium were the most responsive to organic fertilization and the accumulation of most of the macro and micro elements, followed by orange trees grafted on the same rootstock, while it was noted that mandarin trees grafted on Citrus aurantium were the least responsive among the three types, and this may be due to the effect of the rootstock [14]. The results agree with [15] in the effect of the rootstock on the efficiency of the use of elements in lemon seedlings grafted on different citrus roots, and with [16], In the difference rootstock effect on the leaf mineral content, as they indicated a significant Fe accumulation increase in orange leaves than in lemon, this was attributed to the rootstock affect. Organic waste greatly affects the physical and chemical properties and fertility of the soil, as it enriches it with the elements that are necessary for the growth of plants, as well as the temporary change of soil acidity and affecting its buffering capacity, which due to absorb microelements, especially in the base soils [17], this may explain the plants leaf content of both macro and micro elements, as the tables indicate.…”
Section: Discussionsupporting
confidence: 68%
“…No significant reduction was reported in the case of SA alone with all combinations of citrus species and rootstock. Sáenz-Pérez et al [ 52 ] reported that C. aurantium rootstock is not suitable for lemon and sweet orange since it had the highest level of CLas titer. However, C. macropylla and C. volkameriana showed lower Cq values.…”
Section: Discussionmentioning
confidence: 99%